Functional expression of TRPM7 as a Ca2+ influx pathway in adipocytes - Hana Inoue; Masato Inazu; Masato Konishi; Utako Yokoyama (Physiological Reports, 2019)
Abstract In adipocytes, intracellular Ca2+ and Mg2+ modulates physiological functions, such as insulin action and the secretion of adipokines. TRPM7 is a Ca2+/Mg2+‐permeable non‐selective cation channel. TRPM7 mRNA is highly expressed in adipose tissue, however, its functional expression in adipocytes remains to be elucidated. In this study, we demonstrated for the first time that TRPM7 was functionally expressed in both freshly isolated white adipocytes and in 3T3‐L1 adipocytes differentiated from a 3T3‐L1 pre‐adipocyte cell line by whole‐cell patch‐clamp recordings. Consistent with known properties of TRPM7 current, the current in adipocytes was activated by the elimination of extracellular divalent cations and the reduction of intracellular free Mg2+ concentrations, and was inhibited by the TRPM7 inhibitors, 2‐aminoethyl diphenylborinate (2‐APB), hydrogen peroxide (H2O2), N‐methyl maleimide (NMM), NS8593, and 2‐amino‐2‐[2‐(4‐octylphenyl)ethyl]‐1,3‐propanediol (FTY720). Treatment with small‐interfering (si) RNA targeting TRPM7 resulted in a reduction in the current to 23 ± 7% of nontargeting siRNA‐treated adipocytes. Moreover a TRPM7 activator, naltriben, increased the TRPM7‐like current and [Ca2+]i in 3T3‐L1 adipocytes but not in TRPM7‐knockdown adipocytes. These findings indicate that TRPM7 is functionally expressed, and plays a role as a Ca2+ influx pathway in adipocytes.